2003
DOI: 10.1210/jc.2002-021734
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and Adipose Tissue Regulatory Peptides: Effect of Gastric Bypass Surgery in Obese Humans

Abstract: Presently surgery is the most effective way to obtain a controlled weight reduction in morbidly obese patients. Roux-en-Y gastric bypass (RYGBP) surgery is effective and used worldwide, but the exact mechanism of action is unknown. The effect of RYGBP on ghrelin, insulin, adiponectin, and leptin levels was investigated in 66 obese subjects; mean weight 127 kg (range, 96-195 kg) and mean body mass index (BMI) 45 kg/m(2) (range, 33-64) before and after surgery. Ghrelin levels were also compared in 10 nonoperated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
169
5
17

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(220 citation statements)
references
References 43 publications
29
169
5
17
Order By: Relevance
“…In the present cross-sectional study, we found higher fasting, morning ghrelin levels in the RYGBP group than in the age-matched morbidly obese, which is in accordance with our previous prospective study in 66 patients before and after gastric bypass. 22 Furthermore, after the extended fast we demonstrated a comparable mealrelated suppression of ghrelin concentrations in the middleaged RYGBP group as in the young non-obese group and a tendency to even larger suppressibility in the operated patients compared to the age-matched non-obese subjects, despite a higher BMI in the RYGBP patients. Explanations for these discrepancies between studies might be differences in magnitude of weight loss or differences in surgical procedures.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…In the present cross-sectional study, we found higher fasting, morning ghrelin levels in the RYGBP group than in the age-matched morbidly obese, which is in accordance with our previous prospective study in 66 patients before and after gastric bypass. 22 Furthermore, after the extended fast we demonstrated a comparable mealrelated suppression of ghrelin concentrations in the middleaged RYGBP group as in the young non-obese group and a tendency to even larger suppressibility in the operated patients compared to the age-matched non-obese subjects, despite a higher BMI in the RYGBP patients. Explanations for these discrepancies between studies might be differences in magnitude of weight loss or differences in surgical procedures.…”
Section: Discussionsupporting
confidence: 51%
“…7,36 In our previous study, we demonstrated a close inverse association between the circulating concentrations of insulin and ghrelin both preoperatively and 6 and 12 months after gastric bypass. 22 In a study in 10 volunteers, postprandial suppression of plasma ghrelin level was shown to be proportional to ingested caloric load who were given liquid meals with widely varied caloric content. 37 As expected, they also found that the ingested caloric load was directly proportional to the area under the curve of plasma insulin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in ghrelin levels post-gastric bypass have also been seen (Garcia-Fuentes et al, 2008;Holdstock et al, 2003;Perez-Romero et al, 2010;Ybarra et al, 2009); however this may be associated with active weight loss rather than the surgery itself (Faraj et al, 2003). Several explanations have been proposed for the conflicting findings regarding ghrelin levels following gastric bypass surgery including differences in pre-operative insulin resistance, surgical methods and post-operative vagal nerve dysfunction (Pournaras & le Roux, 2010;Vincent & le Roux, 2008).…”
Section: Ghrelin and Bariatric Surgerymentioning
confidence: 99%
“…10 The medical treatment of obesity, in particular morbid obesity (BMI Z40 kg/m 2 ), is unsatisfactory and has led to the increased use of surgery worldwide. 11 Roux-en-Y gastric bypass (RYGBP) causes a marked reduction in adipose tissue mass, 12 alters adipose tissue regulatory hormones 13 and reduces morbidity. 14 The changes in body weight and metabolic balance provide a useful study group from which we can examine interactions between obesity, insulin resistance (as indicated by a high HOMA index; ie.…”
Section: Introductionmentioning
confidence: 99%